First comes love [compact disc, unabridged] : a novel - Giffin, Emily (Books on Tape ; Random House Audio, 2016)
"Meredith thought she'd done it all right - married the perfect man, had the perfect daughter - but as she grows increasingly restless, she can't help but wonder if she got the love part wrong. Josie has been happily single for years, but she wants a child of her own so much she's one bad Match.com date away from heading straight for the baby carriage all on her own. The sisters, whose relationship was strained by the tragic death of their older brother over a decade ago, find that they need each other more than they realized"--